A preparation method and application of nitrogen-containing titanium alloy by additive manufacturing

By using a nitride-inert gas mixed atmosphere during the SLM molding process, the problem of degradation of mechanical properties of titanium alloy in high temperature environment is solved, and excellent mechanical properties under high temperature conditions are achieved.

CN119057080BActive Publication Date: 2025-04-01NINGBO ZHONGKE XIANGLONG LIGHTWEIGHT TECH CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411571107.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-04-01
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

Existing titanium alloys show a problem of degradation in high temperature environments, which is difficult to meet the needs of ultra-high-speed aircraft under high temperature, high stress and strong wear conditions.

Method used

Through additive manufacturing technology, a nitrogen-containing titanium alloy is formed during the SLM molding process using a nitride-inert gas mixture atmosphere, the content of N elements is regulated, and heat treatment is carried out to improve mechanical properties.

Benefits of technology

It significantly improves the mechanical properties of titanium alloy at room temperature and high temperatures, including tensile strength, yield strength and elongation, and can maintain high mechanical properties in an environment of 550~700℃.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119057080B_ABST
    Figure CN119057080B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of additive manufacturing of titanium alloy structural parts, and relates to a preparation method of additively manufactured nitrogen-containing titanium alloy and its application. A preparation method of additively manufactured nitrogen-containing titanium alloy, comprising the following steps: filling a nitride-inert gas mixed atmosphere into an SLM molding chamber, melting and solidifying titanium-based material powder layer by layer through SLM technology to form an additively manufactured nitrogen-containing titanium alloy; the nitride-inert gas mixed atmosphere is formed by nitride powder being dispersed in an inert gas. The present invention mixes nano-sized nitride powder with an inert gas to obtain a nitride-inert gas mixed atmosphere, which can be used as a protective atmosphere in the SLM forming process, thereby preparing a nitride-modified titanium alloy, wherein the nitride strengthening phase is evenly distributed in the matrix, has a strong bonding with the matrix, and is conducive to improving mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of additively manufactured titanium alloy structural parts, and relates to a preparation method of additively manufactured nitrogen-containing titanium alloy and application thereof. Background Art

[0002] Titanium and titanium alloys have the characteristics of low density, high specific strength, corrosion resistance and excellent high-temperature mechanical properties. They are increasingly widely used in heavy-duty fuselage structures, jet engines, and gas turbines in the fields of aerospace, marine engineering, and chemical engineering. The alloying method has significantly improved the performance of titanium alloys, and the service temperature has been increased from 350°C to 400°C, but it has not been able to break through the 600°C bottleneck in the past 30 years. With the rapid development of aerospace technology, ultra-high-speed aircraft need to work under more extreme conditions such as ultra-high temperature, high stress, and strong wear, which puts more stringent requirements on the strength, stiffness, heat resistance and other properties of titanium-based materials.

[0003] In the actual production process, due to the need for specific properties of titanium alloys, adding a certain amount of metal elements to pure titanium is one of the most common methods. The type and concentration of the added elements can be used to adjust the microstructure and properties of the alloy. The added metal elements can generally be divided into the following three types:

[0004] (1) α-stabilizing elements: including Al, B, Ga, Ge, O, N, C, etc. Their main function is to expand the α phase region by increasing the phase transition temperature of titanium alloys. Al is a more commonly used element. Appropriate addition of Al can adjust the strength of titanium alloys, but the amount of Al added should not exceed 7%, otherwise it is easy to form Ti3Al phase, causing the alloy to be easily brittle and fractured. O, N, and C all have a certain effect on improving the strength of titanium alloys. N elements can react with the matrix in situ to generate TiN, or they can be dissolved in the titanium alloy matrix in the form of interstitial atoms, but excessive N elements will damage the plasticity of titanium alloys.

[0005] (2) β-stabilizing elements: β-stabilizing elements are the opposite of α-stabilizing elements. The existence of β-stabilizing elements is mainly to reduce the phase transition point temperature and expand the β phase region. β-stabilizing elements are generally divided into isomorphous β-stabilizing elements and eutectoid β-stabilizing elements. The obvious feature of isomorphous β-stabilizing elements is that they have the same Mo and V as Ti. Mo and V have the most obvious effect in improving β-stabilization. Nb is not as effective as Mo in strengthening titanium alloys, but it is often used in Ti-Al alloys to improve the plasticity and toughness of the alloy. Ta is rarely used, mainly because of its weak strengthening effect, but adding a small amount of alloys can improve oxidation resistance and corrosion resistance. Eutectoid β-stabilizing elements can cause eutectoid transformation, generally including Cr, Mn, Fe, Si, Cu, H, Ni, Ag and other elements. Among them, Cr, Mn, Fe and other elements have a slow eutectoid reaction rate with Ti. It is difficult to start the eutectoid transformation under conventional heat treatment processes, so they are also called inactive eutectoid elements. Elements such as Si, Cu, H, Ni, and Ag react quickly with Ti and are very easy to carry out, so they are also called active eutectoid elements. Active eutectoid elements are difficult to inhibit because of their fast eutectoid reaction. Fe is more common and has a good stabilizing effect on the β phase, but its thermal stability is weak, which limits its application. The widely used Cr element can improve the strength and plasticity of titanium alloys, and can strengthen the structure and performance through heat treatment. Si is also a commonly used β-stabilizing element, which can improve the thermal strength and heat resistance of titanium alloys. It is generally widely used in high-temperature titanium alloys. H has a great damage to the performance of titanium alloys, and its content needs to be strictly controlled. Titanium and H are easy to generate TiH, which leads to a significant decrease in the brittleness of the alloy, so the H content is generally required to be below 0.012, and H can be removed by vacuum annealing at high temperature.

[0006] (3) Neutral elements: Neutral elements have little effect on the β transition temperature. Commonly used elements include Zr, Sn, and Hf. The crystal structure of Zr is similar to that of Ti. It can form a solid solution with Ti and play a role in solid solution strengthening of titanium alloys.

[0007] Titanium alloys are classified differently according to different standards. Generally, they are classified according to the microstructure state after annealing, and can be roughly divided into three types: α, (α+β), and β. my country has corresponding titanium alloy grades of TA, TC, and TB. The main titanium alloys currently used include Ti6Al4V (TC4). TC4 is an α+β two-phase titanium alloy. Because of its good strength-to-weight ratio and excellent corrosion resistance, this lightweight alloy occupies a dominant position. Although the alloying regulation of titanium can improve the grain boundary strength at room temperature, as the temperature rises to above 400°C, the significant weakening of the grain boundary strength has become one of the factors that reduce heat resistance. Therefore, titanium alloy materials urgently need to improve their high-temperature performance to meet the service performance requirements of their components. At the same time, how to prepare high-performance titanium alloy complex structural parts has become a key issue in the development of manufacturing technology.

[0008] The manufacturing process and forming technology of traditional titanium alloy structural parts are equal material manufacturing and subtractive manufacturing processes, but both processes have serious material waste, long production process, expensive equipment and can not meet the defects of complex structural parts production, which seriously hinder the deeper development of titanium alloy in more fields. Additive manufacturing technology (AM) emerged in the 1990s and has been developing since then. This technology uses rapid prototyping technology. The powder raw material is melted layer by layer by laser, and then a molten structure is generated on the surface of the part, and finally the entire solid part is built. Additive manufacturing technology has a high degree of design freedom and a manufacturing method for new geometric shapes, and does not require any tools or fixtures during the forming process, which is difficult to achieve with traditional processing methods. LPBF (laser powder bed fusion) additive manufacturing technology is one of AM, using metal powder as raw material. Its laser heat source is usually controlled by an optical system, which selectively scans the pre-laid powder bed and melts / sinters the material through lens convergence and galvanometer reflection. At the same time, in order to prevent metal oxidation at high temperature, Ar is used as a protective gas in the closed working chamber to circulate and take away splashing smoke and excess heat. The laser selective melting technology (SLM technology) based on the high scanning speed of the laser beam (up to 5m / s) is currently the most widely used LPBF technology. One of the more remarkable advantages of SLM technology is that the Gaussian laser heat source used has the characteristics of high input energy per unit area and small irradiation range, which can achieve dimensional accuracy that traditional technologies do not have, and realize the forming of high-performance complex aluminum alloy components. Another feature of SLM is that the molten pool heats and cools quickly during the forming process, which can achieve a higher cooling rate and solidification rate (106-108 K / s), making it easy to obtain a finer microstructure than in traditional manufacturing processes, which can significantly improve the comprehensive service performance of titanium alloys. At present, the research on SLM forming of titanium alloys is mostly focused on the influence of process parameters on forming accuracy, residual porosity, microstructure evolution, static mechanical properties (tensile properties, compression properties, friction and wear properties), etc.

[0009] The composite method of introducing multi-element and multi-size ceramic reinforcement phase particles and regulating their orderly spatial arrangement is one of the effective methods to improve the performance of titanium alloys. TiB, TiC and rare earth oxides (such as La2O3, etc.) are commonly used ceramic reinforcement phases in titanium alloys, which are usually generated by in-situ spontaneous reactions between titanium alloy matrix and B, C, LaB6, etc. during the preparation process. Through flexible component design, sophisticated distribution, structural optimization and various deformation processing control, the synergistic coupling between tough titanium alloy and high-strength reinforcement can be achieved, thereby showing higher specific strength, specific stiffness and better heat resistance. The use temperature will also be 50~200℃ higher than that of traditional titanium alloys, and it is expected to partially replace traditional nickel-based high-temperature alloys in the use environment of 550~700℃, thereby achieving a significant reduction in weight. Titanium alloy-based composite materials have broad application prospects and development potential in aerospace and other fields, and therefore have received widespread attention. Summary of the invention

[0010] In view of the deficiencies in the prior art, the present invention provides a preparation method of an additively manufactured nitrogen-containing titanium alloy and its application, which effectively improves the mechanical properties of the additively manufactured titanium alloy at room temperature and high temperature.

[0011] One object of the present invention is achieved by the following technical solutions:

[0012] A preparation method for additively manufactured nitrogen-containing titanium alloy, comprising the following steps: filling a nitride-inert gas mixed atmosphere into an SLM molding chamber, melting and solidifying titanium-based material powder layer by layer through SLM technology to form an additively manufactured nitrogen-containing titanium alloy;

[0013] The nitride-inert gas mixed atmosphere is formed by dispersing nitride powder in the inert gas.

[0014] Preferably, the method for preparing the nitride-inert gas mixed atmosphere comprises the following steps: adding nitride powder to a powder mixer having an ultrasonic vibration function, then uniformly dispersing the powder by ultrasonic vibration, and then loading an inert gas to form a nitride-inert gas mixed atmosphere. The frequency of the ultrasonic vibration is preferably 150 to 400 times / min, and the loading flow rate of the inert gas is preferably 1 to 100 L / min.

[0015] Preferably, the nitride is a compound formed by N and one or more of Al, Ti, and B. More preferably, the nitride is one or more of AlN, TiN, and BN. Still more preferably, the nitride is TiN.

[0016] Preferably, the average particle size of the nitride powder is 1 to 1000 nm. More preferably, it is 1 to 500 nm. For example, it can be any value among 1, 2, 5, 8, 10, 20, 30, 40, 50, 60, 70, 100, 150, 200, 250, 300, 350, 400, 450, 500 nm, but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable.

[0017] Preferably, the inert gas is argon and / or helium. More preferably, the purity of argon is ≥99.995%, and the purity of helium is ≥99.995%.

[0018] In the nitride-inert gas mixed atmosphere, nitride and inert gas are mixed in a certain volume percentage to control the N element content in the additively manufactured nitrogen-containing titanium alloy.

[0019] Preferably, the titanium-based material is pure titanium and / or a titanium alloy.

[0020] Preferably, the titanium alloy is a titanium alloy composed of Ti and one or more of Al, V, Sn, Si, Fe, Mo, Mn, Cr, and Ni. Further preferably, the titanium alloy is one or more of TC4, TA15, TC17, and IMI834. Further preferably, the titanium alloy is TC4.

[0021] Preferably, the average particle size of the titanium-based material powder is 5 to 100 μm, and more preferably 15 to 53 μm.

[0022] Preferably, the speed of charging the nitride-inert gas mixed atmosphere into the SLM molding chamber is 0.5~10L / min; more preferably, it is 1~4L / min, for example, it can be any value of 1, 1.5, 2, 2.5, 3, 3.5, 4L / min.

[0023] Before the nitride-inert gas mixed atmosphere is filled into the SLM molding chamber, it is necessary to first fill the SLM molding chamber with inert gas for deoxidation protection.

[0024] Preferably, the parameters of the SLM technology include: laser scanning speed of 400~1800mm / s, laser power of 120~1000w, spot diameter of 80~500μm, laser scanning spacing of 50~500μm; powder layer thickness of 25~400μm.

[0025] Preferably, the SLM is a top powder feeding machine.

[0026] Preferably, the N content in the additively manufactured nitrogen-containing titanium alloy is in the range of 0.005-1.0 wt %.

[0027] The second object of the present invention is achieved by the following technical solutions:

[0028] A preparation method for an additively manufactured nitrogen-containing titanium alloy component, comprising the following steps: filling a nitride-inert gas mixed atmosphere into an SLM molding chamber, melting and solidifying titanium-based material powder layer by layer through the SLM technology to form an additively manufactured nitrogen-containing titanium alloy, and then performing heat treatment, wherein the heat treatment has a holding temperature of 700-950° C. and a holding time of 1-5 hours, to obtain an additively manufactured nitrogen-containing titanium alloy component;

[0029] The nitride-inert gas mixed atmosphere is formed by dispersing nitride powder in the inert gas.

[0030] Preferably, the temperature is raised to the insulation temperature over 30 to 300 minutes.

[0031] Preferably, the N content in the additively manufactured nitrogen-containing titanium alloy component is in the range of 0.005-1.0 wt %.

[0032] The third object of the present invention is achieved by the following technical solutions:

[0033] An additively manufactured nitrogen-containing titanium alloy is prepared by an additively manufactured nitrogen-containing titanium alloy preparation method.

[0034] Preferably, the additively manufactured nitrogen-containing titanium alloy is a gradient or non-gradient material.

[0035] Preferably, the room temperature tensile strength of the additively manufactured nitrogen-containing titanium alloy can reach 1100~1800MPa, the yield strength can reach 1100~1800MPa, and the elongation is ≥5%.

[0036] Room temperature is defined as 10~40℃.

[0037] The fourth object of the present invention is achieved by the following technical solutions:

[0038] A nitrogen-containing titanium alloy component manufactured by additive manufacturing is prepared by a preparation method of a nitrogen-containing titanium alloy component manufactured by additive manufacturing.

[0039] Preferably, the additively manufactured nitrogen-containing titanium alloy is a gradient or non-gradient material.

[0040] Preferably, the room temperature tensile strength of the additively manufactured nitrogen-containing titanium alloy component can reach 1100~1800MPa, the yield strength can reach 1100~1800MPa, and the elongation is ≥5%.

[0041] Preferably, the additively manufactured nitrogen-containing titanium alloy component can have a tensile strength of 700-1000 MPa, a yield strength of 600-900 MPa, and an elongation of ≥10% in a 400°C environment.

[0042] Preferably, the additively manufactured nitrogen-containing titanium alloy component can have a tensile strength of 300-500 MPa, a yield strength of 200-400 MPa, and an elongation of ≥20% in a 600°C environment.

[0043] The fifth object of the present invention is achieved by the following technical solutions:

[0044] An additively manufactured nitrogen-containing titanium alloy component is used in titanium alloy blades and engine blades.

[0045] Compared with the prior art, the present invention has the following beneficial effects:

[0046] 1. The present invention mixes nano-sized nitride powder with an inert gas to obtain a nitride-inert gas mixed atmosphere, which can be used as a protective atmosphere in the SLM forming process, thereby preparing a nitride-modified titanium alloy; and the nitride powder and the inert gas are mixed in different volume ratios, so that the N element content of the SLM-formed titanium alloy component can be accurately controlled. In actual applications, the ratio of nitride powder to inert gas is adjusted according to the application scenario and performance requirements.

[0047] 2. In the additively manufactured nitrogen-containing titanium alloy and components prepared by the present invention, the nitride strengthening phase is evenly distributed in the matrix and has a strong bonding with the matrix, which is beneficial to improving the mechanical properties.

[0048] 3. The additively manufactured nitrogen-containing titanium alloy components prepared by the present invention have excellent mechanical properties at room temperature and still have good mechanical properties in high temperature environments. At room temperature, including but not limited to: room temperature tensile strength can reach 1100~1800MPa, yield strength can also reach 1100~1800MPa, and elongation ≥5%. In a 400℃ environment, the tensile strength can reach 700~1000MPa, the yield strength can reach 600~900MPa, and the elongation is ≥10%. In a 600℃ environment, the tensile strength can reach 300~500MPa, the yield strength can reach 200~400MPa, and the elongation is ≥20%.

[0049] 4. The additively manufactured nitrogen-containing titanium alloy component prepared by the present invention has excellent mechanical properties at 600°C, indicating that it can be used in high-temperature environments, which makes it competent for some parts that need to work under high-temperature conditions, such as aircraft engine blades, etc. It can partially replace traditional nickel-based high-temperature alloys in high-temperature environments, thereby achieving the purpose of significantly reducing weight. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 This is an appearance diagram of a cylindrical additively manufactured nitrogen-containing titanium alloy prepared in the embodiment;

[0051] Figure 2This is the morphology and composition analysis diagram of TiN in the additively manufactured nitrogen-containing titanium alloy prepared in Example 7. DETAILED DESCRIPTION

[0052] The technical scheme of the present invention is further described below by specific examples and accompanying drawings. It should be understood that the specific examples described herein are only used to help understand the present invention and are not intended for specific limitations of the present invention. The accompanying drawings used herein are only for better illustrating the disclosure of the present invention and do not have a limiting effect on the scope of protection. If not otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used raw materials in the art, and the methods used in the embodiments are all conventional methods in the art.

[0053] In the following examples and comparative examples, the main raw material parameters are as follows:

[0054] The average particle size of nano-TiN powder is 60nm, and the purity is 99.9%; the average particle size of TC4 powder is 40μm, and the purity is 99.9%; the purity of argon gas is 99.999%.

[0055] Example 1

[0056] The additively manufactured nitrogen-containing titanium alloy of this embodiment is prepared by the following method:

[0057] The nano-TiN powder was evenly dispersed in a powder mixer by ultrasonic vibration (the frequency of ultrasonic vibration was 250 times / min), and then argon gas was introduced at a gas flow rate of 20 L / min to form a TiN-Ar mixed atmosphere, in which the volume ratio of nano-TiN powder to argon gas was 15%.

[0058] Argon gas was filled into the SLM for deoxidation protection, and then the TC4 powder was transported to the powder cylinder in the SLM molding chamber. Subsequently, the TiN-Ar mixed atmosphere was filled into the SLM molding chamber at a speed of 3L / min. The TC4 powder was printed horizontally by SLM technology to form a cylindrical additive manufacturing nitrogen-containing titanium alloy (size: diameter 12mm, height 75mm, such as Figure 1 As shown in the figure), SLM technical parameters include: laser scanning speed 1300mm / s, laser power 415w, spot diameter 110μm, laser scanning spacing 110μm; powder layer thickness 50μm.

[0059] The nitrogen content in the prepared additively manufactured nitrogen-containing titanium alloy is 0.19wt%.

[0060] Example 2

[0061] The only difference between Example 2 and Example 1 is that Example 2 uses SLM technology to print TC4 powder vertically to form a cylindrical additively manufactured nitrogen-containing titanium alloy, and the rest is the same as Example 1.

[0062] Example 3

[0063] The additively manufactured nitrogen-containing titanium alloy of this embodiment is prepared by the following method:

[0064] The nano-TiN powder was evenly dispersed in a powder mixer by ultrasonic vibration (the frequency of ultrasonic vibration was 250 times / min), and then argon was loaded at 10 L / min to form a TiN-Ar mixed atmosphere, in which the volume ratio of nano-TiN powder to argon was 16%.

[0065] Argon gas is filled into the SLM for deoxidation protection, and then the TC4 powder is transported to the powder cylinder in the SLM molding chamber. Subsequently, the TiN-Ar mixed atmosphere is filled into the SLM molding chamber at a speed of 4L / min. The TC4 powder is printed horizontally through the SLM technology to form a cylindrical additive manufacturing nitrogen-containing titanium alloy (size: 12mm in diameter, 75mm in height). The SLM technical parameters include: laser scanning speed 1400mm / s, laser power 415w, spot diameter 150μm, laser scanning spacing 150μm; powder layer thickness 50μm.

[0066] The nitrogen content in the additively manufactured nitrogen-containing titanium alloy is 0.20wt%.

[0067] Example 4

[0068] The only difference between Example 4 and Example 3 is that Example 4 uses SLM technology to print TC4 powder vertically to form a cylindrical additively manufactured nitrogen-containing titanium alloy, and the rest is the same as Example 3.

[0069] Example 5

[0070] The additively manufactured nitrogen-containing titanium alloy of this embodiment is prepared by the following method:

[0071] The nano-TiN powder was evenly dispersed in a powder mixer by ultrasonic vibration (the frequency of ultrasonic vibration was 250 times / min), and then argon was loaded at 30 L / min to form a TiN-Ar mixed atmosphere, in which the volume ratio of nano-TiN powder to argon was 20%.

[0072] Argon gas is filled into the SLM for deoxidation protection, and then the TC4 powder is transported to the powder cylinder in the SLM molding chamber. Subsequently, the TiN-Ar mixed atmosphere is filled into the SLM molding chamber at a speed of 1L / min. The TC4 powder is printed horizontally through the SLM technology to form a cylindrical additive manufacturing nitrogen-containing titanium alloy (size: 12mm in diameter, 75mm in height). The SLM technical parameters include: laser scanning speed 1400mm / s, laser power 435w, spot diameter 90μm, laser scanning spacing 80μm; powder layer thickness 50μm.

[0073] The nitrogen content in the additively manufactured nitrogen-containing titanium alloy is 0.24wt%.

[0074] Example 6

[0075] The only difference between Example 6 and Example 5 is that Example 6 uses SLM technology to print TC4 powder in a vertical direction to form a cylindrical additively manufactured nitrogen-containing titanium alloy, and the rest is the same as Example 5.

[0076] Example 7

[0077] The additively manufactured nitrogen-containing titanium alloy of this embodiment is prepared by the following method:

[0078] The nano-TiN powder was evenly dispersed in a powder mixer by ultrasonic vibration (the frequency of ultrasonic vibration was 250 times / min), and then argon was loaded at 15 L / min to form a TiN-Ar mixed atmosphere, in which the volume ratio of nano-TiN powder to argon was 20%.

[0079] Argon gas is filled into the SLM for deoxidation protection, and then the TC4 powder is transported to the powder cylinder in the SLM molding chamber. Subsequently, the TiN-Ar mixed atmosphere is filled into the SLM molding chamber at a speed of 2L / min. The TC4 powder is printed horizontally through the SLM technology to form a cylindrical additive manufacturing nitrogen-containing titanium alloy (size: 12mm in diameter, 75mm in height). The SLM technical parameters include: laser scanning speed 1450mm / s, laser power 385w, spot diameter 100μm, laser scanning spacing 110μm; powder layer thickness 50μm.

[0080] The nitrogen content in the additively manufactured nitrogen-containing titanium alloy is 0.3wt%.

[0081] Figure 2 The morphology and composition analysis diagram of TiN in the additively manufactured nitrogen-containing titanium alloy prepared in Example 7. It can be seen from the figure that TiN is uniformly dispersed in the titanium alloy matrix. Through EDS micro-area composition analysis, it is found that the atomic ratio of Ti element to N element is still 1:1, and the chemical composition of TiN is not changed during the SLM forming process.

[0082] Example 8

[0083] The only difference between Example 8 and Example 7 is that Example 8 uses SLM technology to print TC4 powder in a vertical direction to form a cylindrical additively manufactured nitrogen-containing titanium alloy, and the rest is the same as Example 7.

[0084] Example 9

[0085] The additively manufactured nitrogen-containing titanium alloy of this embodiment is prepared by the following method:

[0086] The nano-TiN powder was evenly dispersed in a powder mixer by ultrasonic vibration (the frequency of ultrasonic vibration was 250 times / min), and then argon was loaded at 25 L / min to form a TiN-Ar mixed atmosphere, in which the volume ratio of nano-TiN powder to argon was 19%.

[0087] Argon gas is filled into the SLM for deoxygenation protection, and then the TC4 powder is transported to the powder cylinder in the SLM molding chamber. Subsequently, the TiN-Ar mixed atmosphere is filled into the SLM molding chamber at a speed of 2.5L / min. The TC4 powder is printed horizontally through the SLM technology to form a cylindrical additive manufacturing nitrogen-containing titanium alloy (size: 12mm in diameter, 75mm in height). The SLM technical parameters include: laser scanning speed 1350mm / s, laser power 375w, spot diameter 200μm, laser scanning spacing 100μm; powder layer thickness 50μm.

[0088] The nitrogen content in the additively manufactured nitrogen-containing titanium alloy is 0.3wt%.

[0089] Example 10

[0090] The only difference between Example 10 and Example 9 is that Example 10 uses SLM technology to print TC4 powder in a vertical direction to form a cylindrical additive manufacturing nitrogen-containing titanium alloy, and the rest is the same as Example 9.

[0091] Embodiment 11

[0092] According to the process of Example 7, TC4 powder is horizontally printed using SLM technology to form a cylindrical additively manufactured nitrogen-containing titanium alloy. The temperature is then raised to 850°C for 100 minutes for heat treatment, kept warm for 3 hours, and cooled to room temperature with the furnace to obtain a cylindrical additively manufactured nitrogen-containing titanium alloy component.

[0093] Example 12

[0094] According to the process of Example 8, TC4 powder is printed vertically by SLM technology to form a cylindrical additively manufactured nitrogen-containing titanium alloy, and then the temperature is raised to 850°C for 100 minutes for heat treatment, kept warm for 3 hours, and cooled to room temperature with the furnace to obtain a cylindrical additively manufactured nitrogen-containing titanium alloy component.

[0095] Embodiment 13

[0096] According to the process of Example 10, TC4 powder is printed vertically by SLM technology to form a cylindrical additively manufactured nitrogen-containing titanium alloy, and then the temperature is raised to 850°C for 100 minutes for heat treatment, kept warm for 3 hours, and cooled to room temperature with the furnace to obtain a cylindrical additively manufactured nitrogen-containing titanium alloy component.

[0097] Comparative Example 1

[0098] The difference between Comparative Example 1 and Example 7 is that no nitride is added in Comparative Example 1, and the specific process is as follows:

[0099] Argon gas is filled into the SLM for deoxidation protection, and then the TC4 powder is transported to the powder cylinder in the SLM molding chamber. Subsequently, Ar gas is filled into the SLM molding chamber at a speed of 2L / min. The TC4 powder is printed horizontally through the SLM technology to form a cylindrical additive manufacturing titanium alloy (size: 12mm in diameter, 75mm in height). The SLM technical parameters include: laser scanning speed 1450mm / s, laser power 385w, spot diameter 100μm, laser scanning spacing 110μm; powder layer thickness 50μm.

[0100] Comparative Example 2

[0101] The difference between Comparative Example 2 and Comparative Example 1 is that Comparative Example 2 prints in the vertical direction to form a cylindrical additively manufactured titanium alloy, and the rest is the same as Comparative Example 1.

[0102] Comparative Example 3

[0103] The difference between Comparative Example 3 and Comparative Example 1 is that in Comparative Example 3, TC4 powder is horizontally printed through SLM technology to form a cylindrical additively manufactured titanium alloy, and then the temperature is raised to 850°C for heat treatment for 100 minutes, kept warm for 3 hours, and cooled to room temperature with the furnace to obtain a cylindrical additively manufactured titanium alloy component.

[0104] Comparative Example 4

[0105] The difference between Comparative Example 4 and Comparative Example 2 is that in Comparative Example 4, TC4 powder is printed vertically through SLM technology to form a cylindrical additively manufactured titanium alloy, and then the temperature is raised to 850°C for heat treatment for 100 minutes, kept warm for 3 hours, and cooled to room temperature with the furnace to obtain a cylindrical additively manufactured titanium alloy component.

[0106] The additively manufactured nitrogen-containing titanium alloys of Examples 1-10 before heat treatment, the additively manufactured nitrogen-containing titanium alloy components of Examples 11-13 after heat treatment, the additively manufactured titanium alloys of Comparative Examples 1-2 before heat treatment, and the additively manufactured titanium alloy components of Comparative Examples 3-4 after heat treatment were tested for mechanical properties at room temperature (25°C) in accordance with the national standard GB / T228.1, and the results are shown in Table 1. The cylindrical additively manufactured nitrogen-containing titanium alloy components of Examples 11-13 and the additively manufactured titanium alloy components of Comparative Examples 3-4 were tested for mechanical properties at 400°C and 600°C in accordance with the national standard GB / T228.2, and the results are shown in Table 1.

[0107] The mechanical properties test is carried out according to GB-T 228.1-2021 standard.

[0108] Table 1 Mechanical properties of Examples 1-13 and Comparative Examples 1-4 at room temperature, 400°C, and 600°C

[0109]

[0110] It can be seen from Table 1 that the tensile strength of the additively manufactured nitrogen-containing titanium alloy prepared before and after heat treatment in the embodiment of the present invention at room temperature is greater than 1100MPa, the yield strength is also greater than 1100MPa, and the elongation is ≥5%. The additively manufactured nitrogen-containing titanium alloy structural parts prepared after heat treatment have a tensile strength of greater than 700MPa, a yield strength of greater than 600MPa, and an elongation of greater than 12% in a 400°C environment. In a 600°C environment, the tensile strength is greater than 300MPa, the yield strength is greater than 200MPa, and the elongation is greater than 20%.

[0111] The additively manufactured nitrogen-containing titanium alloy prepared before and after heat treatment in the embodiment of the present invention has significantly improved mechanical properties measured at room temperature, 400° C., or 600° C. compared to the nitrogen-free titanium alloy.

[0112] Additively manufactured nitrogen-containing titanium alloy structural parts can be printed in both the horizontal and vertical directions, and the tensile strength is not much different.

[0113] The various aspects, embodiments, and features of the present invention should be considered to be illustrative in all aspects and not limiting of the present invention, the scope of which is defined solely by the claims. Other embodiments, modifications, and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.

[0114] In the preparation method of the present invention, the order of each step is not limited to the order listed. For those skilled in the art, without creative work, the order of each step is also within the protection scope of the present invention. In addition, two or more steps or actions can be performed simultaneously.

[0115] Finally, it should be noted that the specific embodiments described herein are merely examples of the present invention, and are not intended to limit the implementation methods of the present invention. A person skilled in the art of the present invention may make various modifications or supplements to the specific embodiments described, or replace them in a similar manner. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.

Claims

1. A method for preparing a nitrogen-containing titanium alloy by additive manufacturing, characterized in that: The following steps are involved: A nitride-inert gas mixed atmosphere is filled into the SLM molding chamber, and the titanium-based material powder is melted and solidified layer by layer through the SLM technology to form an additively manufactured nitrogen-containing titanium alloy; The nitride-inert gas mixed atmosphere is formed by dispersing nitride powder in the inert gas; Nitride is a compound formed by N and one or more of Al, Ti, and B; The titanium-based material is pure titanium and / or titanium alloy, and the titanium alloy is a titanium alloy composed of Ti and one or more of Al, V, Sn, Si, Fe, Mo, Mn, Cr, and Ni; The preparation method of the nitride-inert gas mixed atmosphere comprises the following steps: adding nitride powder into a powder mixer with ultrasonic vibration function, then uniformly dispersing it by ultrasonic vibration, and then loading inert gas to form a nitride-inert gas mixed atmosphere.

2. The preparation method according to claim 1, characterized in that: The nitride is TiN; The titanium-based material is TC4; The average particle size of the nitride powder is 1~1000nm; The average particle size of the titanium-based material powder is 5~100μm.

3. The preparation method according to claim 1, characterized in that: The speed of filling the nitride-inert gas mixed atmosphere into the SLM molding chamber is 0.5~10L / min; The parameters of SLM technology include: laser scanning speed 400~1800mm / s, laser power 120~1000w, spot diameter 80~500μm, laser scanning spacing 50~500μm; powder layer thickness is 25~400μm.

4. The preparation method according to claim 1, characterized in that: The nitrogen content in the additively manufactured nitrogen-containing titanium alloy ranges from 0.005 to 1.0wt%.

5. A method for preparing a nitrogen-containing titanium alloy component by additive manufacturing, characterized in that: The following steps are involved: A nitride-inert gas mixed atmosphere is filled into an SLM molding chamber, and titanium-based material powder is melted and solidified layer by layer by SLM technology to form an additively manufactured nitrogen-containing titanium alloy, and then heat-treated at a holding temperature of 700-950° C. for 1-5 hours to obtain an additively manufactured nitrogen-containing titanium alloy component; The nitride-inert gas mixed atmosphere is formed by dispersing nitride powder in the inert gas; Nitride is a compound formed by N and one or more of Al, Ti, and B; The titanium-based material is pure titanium and / or titanium alloy, and the titanium alloy is a titanium alloy composed of Ti and one or more of Al, V, Sn, Si, Fe, Mo, Mn, Cr, and Ni; The preparation method of the nitride-inert gas mixed atmosphere comprises the following steps: adding nitride powder into a powder mixer with ultrasonic vibration function, then uniformly dispersing it by ultrasonic vibration, and then loading inert gas to form a nitride-inert gas mixed atmosphere.

6. The preparation method according to claim 5, characterized in that: The nitride is TiN; The titanium-based material is TC4; The average particle size of the nitride powder is 1~1000nm; The average particle size of the titanium-based material powder is 5~100μm.

7. The preparation method according to claim 5, characterized in that: The speed of filling the nitride-inert gas mixed atmosphere into the SLM molding chamber is 0.5~10L / min; The parameters of SLM technology include: laser scanning speed 400~1800mm / s, laser power 120~1000w, spot diameter 80~500μm, laser scanning spacing 50~500μm; powder layer thickness is 25~400μm.

8. The preparation method according to claim 5, characterized in that: The nitrogen content in additively manufactured nitrogen-containing titanium alloy components ranges from 0.005 to 1.0 wt%.

9. An additive manufacturing method for a nitrogen-containing titanium alloy, characterized in that: It is prepared by the preparation method described in claim 1.

10. An additively manufactured nitrogen-containing titanium alloy component, characterized in that: It is prepared by the preparation method described in claim 5.

11. The additively manufactured nitrogen-containing titanium alloy component according to claim 10, characterized in that: The room temperature tensile strength of the additively manufactured nitrogen-containing titanium alloy component is 1100-1800 MPa, the yield strength is 1100-1800 MPa, and the elongation is ≥5%; The additively manufactured nitrogen-containing titanium alloy component has a tensile strength of 700-1000 MPa, a yield strength of 600-900 MPa, and an elongation of ≥10% in a 400°C environment; The additively manufactured nitrogen-containing titanium alloy component has a tensile strength of 300-500 MPa, a yield strength of 200-400 MPa, and an elongation of ≥20% in an environment of 600°C.

12. Application of the additively manufactured nitrogen-containing titanium alloy component according to claim 10 in titanium alloy blades and engine blades.

Citation Information

Patent Citations

  • Nano-particle reinforced titanium-based composite material based on SLM forming and preparation method thereof

    CN113215441A

  • Rapid forming method for cylindrical part of 750 DEG C-resistant titanium-based composite material

    CN113510242A

  • Gas protection method for wire powder synchronous feeding additive manufacturing

    CN115351293A